Penguatan Budaya Islam dalam Sistem Pendidikan Sekolah Negeri - Sunarti; Suyatman (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
This research discusses the strengthening of Islamic culture in the public-school education system in Indonesia, which is important in the midst of the challenges of globalization and moral degradation. The purpose of the research is to examine and analyze the application of Islamic values in character education in order to form individuals who have faith, piety, and noble character. The method used is literature research with a descriptive qualitative approach, which involves the identification, classification, and analysis of related literature. The results of the study show that the integration of Islamic values in the curriculum and extracurricular activities can create a harmonious educational environment and support the formation of students' character. The implications of this study emphasize the need for an inclusive strategy in the application of Islamic culture in public schools, so that education not only focuses on academic aspects, but also on moral and ethical development, which is essential to produce a qualified and civilized generation.